(untitled) - Kiplinger, Austin H. (Washington, D.C., 1989)
Book shows the authors briefly look at the current economic picture at home and abroad and describe expected changes in U.S.-Japan relations; demography; health care; education; key industries; labor markets; and investment opportunities. This upbeat, interesting, and informative book offers readers suggestions on how to profit from the enormous changes ahead in the 1990s
Keywords: Economic forecasting,Dự báo kinh tế,Investments,Đầu tư; United States,Hoa Kỳ,United States,Hoa Kỳ